2004
DOI: 10.1158/1078-0432.ccr-1092-03
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of FAS System Is Related to Adverse Clinical Outcome in Stage I-II Breast Cancer Patients Treated with Adjuvant Anthracycline-Based Chemotherapy

Abstract: Purpose: To determine the prognostic value of Fas receptor and Fas ligand (FasL) as apoptosis-related biomarkers in the context of chemoresponsiveness in breast cancer (BC) patients submitted to anthracycline-based adjuvant therapy.Experimental Design: Fas and FasL were investigated by immunohistochemistry in surgical samples collected from 167 stage I-IIa-b BC patients enrolled in a prospective clinical trial using epirubicin plus cyclophosphamide in the adjuvant setting.Results: Fas and FasL were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Another explanation of this observation is brought by in vitro studies, in which it was shown that apoptosis in response to different cytotoxic drugs is also triggered through an autocrine/paracrine mechanism, by an intact Fas system activation pathway [23]. This result is in accordance with suggestion of some preclinical studies showing that surface death receptors (Fas) play key role in drug-induced apoptosis of solid tumor and leukemia [24].…”
Section: Discussionsupporting
confidence: 81%
“…Another explanation of this observation is brought by in vitro studies, in which it was shown that apoptosis in response to different cytotoxic drugs is also triggered through an autocrine/paracrine mechanism, by an intact Fas system activation pathway [23]. This result is in accordance with suggestion of some preclinical studies showing that surface death receptors (Fas) play key role in drug-induced apoptosis of solid tumor and leukemia [24].…”
Section: Discussionsupporting
confidence: 81%
“…In breast cancer patients, Botti et al . noted significantly shorter disease-free and overall survival periods in 167 FAS-negative and FASL-positive stage I/II breast cancer patients (40). In contrast, higher expression levels of FAS are associated with smaller tumor size, negative lymph nodes and prolonged disease-free survival (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, such parallel behavior contradicts to a certain degree what has been published for other tumors. Several authors have reported that solid tumors usually express elevated levels of FasL but reduced levels of Fas receptor (31,32). Up-regulation of FasL has been linked to some advantage for tumor cells through the triggering of apoptosis-independent pathways, resulting in up-regulation of antiapoptotic and tumorigenic genes and/or an increase in motility and invasiveness, particularly for apoptosis-resistant tumor cells (33).…”
Section: Discussionmentioning
confidence: 99%